Pandemic and information and communication technologies to reduce bias of university graduates - Manrique Tejada, Ingrid María (2022)
Objective: To analyze how the pandemic is timely for information and communication technologies to facilitate the development of theses and reduce the bias between graduates and graduate graduates. Material and methods: The results of a study comparing the influence of academic, social and economic factors on the development of research work by students and graduates of graduate schools were used, as well as a proposal for change to improve research output indicators in graduate students, and an interview with members of the Peruvian Society of Science and Innovation and the Preferred Reporting Items for Systematic reviews and Meta-Analyses methodology. The questionnaire has five items, with a Likert scale of 5 levels, where 1 is the lowest grade and 5 the highest. Results: The use of ICT by teachers of thesis course dictation (score 3.5), teaching in the use of repositories and internet resources for the state of the art in the thesis course (score 3.4), the times of documentation in the university (score 3.5), the procedure times of the reviewers, dictaminators and advisors (score 3.3), were regular and with a rating less than expected, only the fifth item, academic motivation to conclude the thesis, obtained a value of 4.2, which was expected. Conclusion: Information and communication technologies regular ly facilitated the development of graduate theses. It is necessary to implement a software since they enter, to accompany the development of the thesis.